2017
DOI: 10.47405/aswj.v2i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Life of LGBT Community in Curup Rejang Lebong Regency of Bengkulu Province

Abstract: Lesbian, Gay, Bisexual, and Transgender, or we known as LGBT is one of community that has vulnerability life. This research indicates that besides interacting and experiencing various disorders in social intersection aspects with family and society, healthy, education and work aspects, actually the LGBT’s community also has adaptation ability even utilizing to increase their well-being. Base on that, should be made social protection efforts through various activities of capacity building a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A study on the presence of transgender women found that LGBT people in Bengkulu numbered in the hundred of thousand. Rejang Lebong has numerous LGBT and even created its own community, the Rejang Lebong Waria Family Association or IKWRL (Osira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the presence of transgender women found that LGBT people in Bengkulu numbered in the hundred of thousand. Rejang Lebong has numerous LGBT and even created its own community, the Rejang Lebong Waria Family Association or IKWRL (Osira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%